Review Artikel: Emulgator Dengan Penggunaan Bahan Alam Terhadap Stabilitas Sediaan Farmasi: Emulgator Dengan Penggunaan Bahan Alam - Pramesty, Dwinda; Siahaan, Desy; FN, Gina; TP Sella, Arinda; Saputro, M. Ramadhan; Pratama, Reza (Jurnal Medika Farmaka, 2025)
ntroduction: Emulsifiers are important components in pharmaceutical formulations, functioning to stabilize two-phase systems such as oil and water. Until now, synthetic emulsifiers have been widely used due to their effectiveness, but they have limitations in terms of safety and sustainability. Therefore, the use of natural emulsifiers is a potential alternative that is safer and more environmentally friendly. This article aims to review the potential and effectiveness of natural emulsifiers on the stability of various pharmaceutical preparations. Methods: The study was conducted through online literature searches on the Google Scholar, ScienceDirect, PubMed, and ResearchGate databases, covering publications from the last 10 years. The keywords used included “emulsifier” “natural ingredients”, and “natural emulsifiers”. Relevant articles were selected based on their relevance to the topic of pharmaceutical emulsion stability. Results: Based on the results of the review, natural emulsifiers such as polysaccharides (gum arabic, alginate, chitosan), proteins (soy lecithin, whey protein, vegetable protein), and plant saponins can improve the physical, chemical, and thermal stability of emulsion preparations. The mechanism is through the formation of a strong interface layer that prevents coalescence, flocculation, and phase separation. Additionally, some natural emulsifiers also possess additional biological activities such as antioxidant and antimicrobial properties. Conclusion: Natural emulsifiers show great potential as alternatives to synthetic emulsifiers in pharmaceutical formulations. Further research is needed to optimize the combination of natural ingredients, homogenization methods, and the development of sustainable emulsions based on natural ingredients.